Disease‐modifying agents for multiple sclerosis and the risk for reporting cancer: A disproportionality analysis using the US Food and Drug Administration Adverse Event Reporting System database. Issue 12 (2nd June 2021) - Stamatellos, Vasileios‐Periklis; Siafis, Spyridon; Papazisis, Georgios
Abstract : Aim: While the efficacy of disease‐modifying therapies (DMTs) for patients with multiple sclerosis (MS) is established, little is known about their long‐term safety. Cancer‐risk after DMT use remains unclear. This study aimed to investigate whether the prescription of DMTs for patients with MS increases the risk of reporting cancer. Methods: Data from the Food and Drug Administration Adverse Event Reporting System were extracted from 2004 to 2020. After data cleaning, the crude and adjusted reported odds ratios (cROR and aROR) for cancer were calculated for DMTs with Interferon beta‐1a as the reference drug. Sensitivity analyses investigated the group of reports with multiple registered DMTs, the effect of indication restriction and the results when using the rest of the DMTs as reference. Results: For malignant tumours, aROR (95% confidence interval [CI]) values were Cladribine 0.46 (0.18‐0.95), Dimethyl fumarate 0.30 (0.27‐0.34), Fingolimod 0.61 (0.53‐0.70), Glatiramer 0.50 (0.43‐0.58), Alemtuzumab 0.84 (0.64‐1.08), Interferon beta‐1b 0.49 (0.42‐0.56), Natalizumab 0.36 (0.34‐0.39), Ocrelizumab 0.48 (0.29‐0.74), Peginterferon beta‐1a 0.35 (0.26‐0.48), Siponimod 0.89 (0.47‐1.54) and Teriflunomide 0.25(0.21‐0.30) adjusted to age, gender and concomitant medications. In the sensitivity analysis, when the rest of the drugs were used as a reference, Interferon beta‐1a and Peginterferon beta‐1a had aROR (95% CI) 2.60 (2.47‐2.74, P < .001) and Alemtuzumab had aROR 1.47 (1.13‐1.88, I = .003). Conclusions: No safety signal for increased cancer risk was detected among the approved DMTs. A potential safety signal detected in the sensitivity analysis concerning Interferon beta‐1a and Alemtuzumab requires further evaluation with more robust evidence.